2020
DOI: 10.1093/jmcb/mjaa046
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of Wnt signaling antagonists and p21-activated kinase enhances cardiomyocyte proliferation during zebrafish heart regeneration

Abstract: Heart regeneration occurs by dedifferentiation and proliferation of pre-existing cardiomyocytes (CMs). However, the signaling mechanisms by which injury induces CM renewal remain incompletely understood. Here, we find that cardiac injury in zebrafish induces expression of the secreted Wnt inhibitors, including Dickkopf 1 (Dkk1), Dkk3, secreted Frizzled-related protein 1 (sFrp1), and sFrp2, in cardiac tissue adjacent to injury sites. Experimental blocking of Wnt activity via Dkk1 overexpression enhances CM prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…On the one hand, Wnt is generally considered to be a proproliferative factor, and Wnt activation has been shown to be beneficial for zebrafish fin and spinal cord regeneration 33,45 . On the other hand, the role of Wnt signalling in cardiomyocyte dedifferentiation and proliferation is controversial [46][47][48] . We hypothesized that Wnt might exert its complex functions by regulating activation of proregenerative cell states, and we investigated whether cells with a shared lineage origin exhibited similar changes following a stimulus, that is, whether lineage relationship is predictive of perturbation response.…”
Section: Identification Of Proregenerative Cardiac Fibroblastsmentioning
confidence: 99%
“…On the one hand, Wnt is generally considered to be a proproliferative factor, and Wnt activation has been shown to be beneficial for zebrafish fin and spinal cord regeneration 33,45 . On the other hand, the role of Wnt signalling in cardiomyocyte dedifferentiation and proliferation is controversial [46][47][48] . We hypothesized that Wnt might exert its complex functions by regulating activation of proregenerative cell states, and we investigated whether cells with a shared lineage origin exhibited similar changes following a stimulus, that is, whether lineage relationship is predictive of perturbation response.…”
Section: Identification Of Proregenerative Cardiac Fibroblastsmentioning
confidence: 99%
“…Activated β-catenin is closely linked to cell proliferation ( 24 , 29 ). To explore the role of Cypher in cardiomyocyte proliferation, RT-qPCR for cell cycle-related genes was performed on both untreated and Cypher siRNA-treated H9C2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Activated β-catenin promotes biological processes such as proliferation, angiogenesis, metastasis, and apoptosis inhibition ( 24 – 26 ). Phosphorylation of β-catenin at Ser675 was reported to activate β-catenin and enhance cardiomyocyte proliferation ( 29 ). We observed that cardiomyocyte proliferation was suppressed by Cypher deficiency ( Figures 5F–J ), which is consistent with the “regulation of cell proliferation” enrichment in GO annotation for downregulated proteins ( Figure 2D ).…”
Section: Discussionmentioning
confidence: 99%
“…CSNK1A1, PAK2, and IKBKB have serine/threonine protein kinase activity and play an important role in intracellular signal transduction. Studies have demonstrated that CSNK1A1 and PAK2 phosphorylate β-catenin at Ser45 and Ser675, respectively, thereby inhibiting the WNT signaling pathway ( 39 , 40 ). IKBKB regulates the immune response by inducing IkB-a phosphorylation at Ser32 and Ser36 through the classical activation pathway to promote NF-κB signal transduction ( 41 ).…”
Section: Discussionmentioning
confidence: 99%